Development of high-temperature heavy density dolerite concrete for 4th generation nuclear power plants - Khan, Muhammad Nasir Ayaz; Malik, Azhar Hussain; Yaqub, Muhammad; Umar, Muhammad; Noman, Muhammad; Abid, Muhammad; Alabduljabbar, Hisham; Mohamed, Abdullah; Zaidi, Syed Salman Ahmad (Frontiers in Materials, 2023)
This study examines the physical, mechanical, microstructural, and attenuation properties of high-density concrete exposed to temperatures ranging from 200 to 1200 °C. For this objective, heavy-density concrete containing 25%, 50%, 75%, and 100% dolerite aggregates was developed and compared with three ordinary concrete mixes. Pre- and post-heated concrete specimens were evaluated for a slump, mass and density loss, compressive strength, rebound hammer, X-ray and gamma-ray attenuation, Half Value Layer (HVL), and Ten Value Layer (TVL) along with microstructural properties determined by scanning electron microscopy and Energy Dispersive X-ray. The incorporation of 75% dolerite aggregate during pre- and post-heating yielded higher mechanical qualities, based on the findings of an experiment. For the same mixture, significant gamma-ray attenuation was measured, allowing for a reduction in radiation shield thickness. It was found that the dolerite heavy-density concrete is a potential radiation shield at high temperatures ranging from 200 – 1200 °C in fourth-generation nuclear power plants.